2014
DOI: 10.1097/mnh.0000000000000051
|View full text |Cite
|
Sign up to set email alerts
|

Is there a new dawn for selective mineralocorticoid receptor antagonism?

Abstract: Purpose of review Aldosterone and the mineralocorticoid receptor contribute to resistant hypertension and cardiovascular mortality, and mineralocorticoid receptor antagonists effectively reduce these complications. Their use is limited in certain populations with a higher risk of hyperkalemia or renal dysfunction. This review will highlight recent developments in extra-renal mineralocorticoid receptor research and the development of novel mineralocorticoid receptor antagonists. Recent findings Tissue-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…Interestingly, nifedipine decreased and stabilized TEER significantly ( Figure 1A). The most likely explanation for this result is that nifedipine can act as an antagonist to the mineralocorticoid receptor, as previously reported, 36 and inhibit some excitation-triggered responses, such as ion secretion.…”
Section: Camentioning
confidence: 77%
“…Interestingly, nifedipine decreased and stabilized TEER significantly ( Figure 1A). The most likely explanation for this result is that nifedipine can act as an antagonist to the mineralocorticoid receptor, as previously reported, 36 and inhibit some excitation-triggered responses, such as ion secretion.…”
Section: Camentioning
confidence: 77%
“…An effort was made by several laboratories during the 1980’s to develop more selective MR antagonists 59, 75 . Roussel-UCLAF developed highly soluble potent 7-alkyl spironolactone MR antagonists which were used for research but were not marketed for clinical use 76, 77 .…”
Section: The First Generation Antagonistsmentioning
confidence: 99%
“…Spironolactone was a significantly better antihypertensive than eplerenone in two clinical studies, perhaps because of its greater potency and longer half-life 59, 114, 115 . Despite side effects, results of clinical trials continue to show therapeutic benefits of MR antagonists in a growing list of conditions 2, 96, 116, 117 , clearly indicating the need for better MR antagonists 59, 75, 118120 . The Dialysis Outcomes Heart Failure Aldactone Study and others have been demonstrated their utility in stemming the progression of chronic kidney disease 121123 .…”
Section: The First Generation Antagonistsmentioning
confidence: 99%
“…Their development and early clinical studies have been reviewed previously, and several drugs have advanced into clinical trials [35,36]. As opposed to most diuretic agents, MRAs do not require filtration to reach their renal epithelial target, and therefore would not be anticipated to lose effectiveness in renal insufficiency.…”
Section: Textmentioning
confidence: 99%
“…This potential benefit must be weighed against the increased risk of hyperkalemia, however. Nonsteroidal MRAs, including finerenone, reduce proteinuria in rodents with a lower incidence of hyperkalemia compared to steroidal MRAs [35,36]. Finerenone has advanced the furthest in clinical trials for treatment of diabetic nephropathy and for heart failure with diabetes or chronic kidney disease [3739].…”
Section: Textmentioning
confidence: 99%